2004
DOI: 10.1520/jfs2003221
|View full text |Cite
|
Sign up to set email alerts
|

Methadone-Related Deaths in Palm Beach County

Abstract: The authors reviewed cases investigated by the Palm Beach Medical Examiner's Office in which postmortem toxicologic studies indicated the presence of methadone over the period from 1998 to 2002, to examine the role of the drug in these deaths. There were 139 methadonepositive cases, including 75 in which the death was attributed to combined drug toxicity and 23 to methadone toxicity alone. Methadone was most frequently used in conjunction with other prescription or illicit drugs, most commonly benzodiazepines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 24 publications
8
39
1
Order By: Relevance
“…Determining exact cause of death is often difficult, 11,62,69 particularly in cases involving methadone. 69 Prescription data are proprietary, and data on adverse events are held privately.…”
Section: Quality Of Evidence and Methodological Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining exact cause of death is often difficult, 11,62,69 particularly in cases involving methadone. 69 Prescription data are proprietary, and data on adverse events are held privately.…”
Section: Quality Of Evidence and Methodological Challengesmentioning
confidence: 99%
“…Determining exact cause of death is often difficult, 11,62,69 particularly in cases involving methadone. 69 Prescription data are proprietary, and data on adverse events are held privately. 57 There is some inconsistency in International Classification of Diseases codes for drug poisoning, as well as a lack of standardization in drug categorization and terminology 57 and coroners' reports.…”
Section: Quality Of Evidence and Methodological Challengesmentioning
confidence: 99%
“…Previous investigators have commented that fatal and nonfatal levels of methadone overlap and that determination of the metabolite, EDDP, did not assist interpretation [1][2][3][4]. We have measured a second methadone metabolite, EMDP, in postmortem cases to gain a better understanding of the accumulation/distribution of this metabolite and also of the overall process of METH demethylation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, after a retrospective review of medical examiner cases involving methadone, Karch and Stephens [1] wrote that ''postmortem measurements of methadone or its metabolite, or both, cannot be used in isolation to identify which deaths are associated with methadone toxicity.'' Similarly, Milroy and Forrest [2], Gagajewski and Apple [3], and Wolf et al [4] reported overlapping methadone concentrations in postmortem tissues in cases where methadone toxicity either was or was not, the cause of death. Greater knowledge of the metabolism and tissue distribution of methadone and its demethylated metabolites may assist in the interpretation of methadone-related deaths.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation